Kalite Maliyetleri ve Muhasebeleştirilmesi - (:unkn) unknown (My University, 2003)
0

The purpose of this paper is to present the cost of quality and its accounting. Many companies in the world gradually promote quality as the central customer value and regard it as a key concept of company strategy in order to achieve the competitive edge. COQ information can be used to indicate major opportunities for corrective action and to provide incentives for quality improvement. The quality costs, can be classified as prevention-appraisal-failure.(PAF) The PAF scheme has been almost universally accepted for quality costing. Quality costs can also be used as part of the strategic business plan. This obviously requires a reporting system. Generally it is not easy to extract quality costs information, from the existing uniform accounting system. The use of the 8th code of account will be more appropriate